MIC-O-MAP: a technology-enhanced learning environment for developing micro-macro thinking skills - Anura B. Kenkre; Sahana Murthy (The Asia-Pacific Society for Computers in Education (APSCE), 2017)
Abstract MIC-O-MAP (MICroscopic-Observations-Macroscopic-Predictions) is a technology-enhanced learning (TEL) environment designed for developing micro-macro thinking skills among science and engineering undergraduate students. Micro-macro thinking involves being able to analyze dynamic processes and interactions on a microscopic level and establish co-relations to the outcomes which we can see and measure in the macroscopic world. In this paper, we report 2 cycles of iterative design, development, and evaluation of MIC-O-MAP, based on a design-based research approach. We first identify the pedagogical design features and learning activities of MIC-O-MAP based on a literature review of the development of micro-macro thinking. We then report an experimental study, which showed positive results that the design features and learning activities of MIC-O-MAP helped students develop micro-macro thinking. This was followed by a detailed interaction analysis, which provided insights into the redesign of MIC-O-MAP. An evaluation of the revised version of MIC-O-MAP showed that the shortcomings of the original version were addressed. The interaction analysis also led us to identify effective actions and learning paths as students learn in interactive TEL environments.